Melchior Wańkowicz’s work: Reflections on the relationship between text and image - Hałaczkiewicz, Joanna (Ruch Literacki, 2024)
This article discusses the relationship between photography and text in Melchior Wańkowicz’s literary reportages. Drawing on the terminology developed in the field of intersemiotic studies, the article concentrates primarily on his books published between 1934 and 1957, i.e. in the interwar period, during the war, and after the war, before his return to Poland. Wankowicz was an enthusiast of the art of photography, and with each successive book experimented more boldly with getting photos into dialogue with the accompanying text. He is most successful in producing a synthesis of picture and word (something akin to the idea of a Gesamtkunstwerk) in Na tropach Smętka [On the Trail of Smętek], Sztafeta - Książka o polskim pochodzie gospodarczym [A Relay Race: A Book about Poland Pushing Ahead with its Economic Plan] and Bitwa o Monte Cassino [The Battle of Monte Cassino]. Of all those books, Sztafeta is exceptional in practically being irreducible to a text-only version.
Keywords: 20th-century Polish literature; text and photography; illustrated reportage; intersemiotics; phototextuality; Melchior Wańkowicz (1892–1974)